FACTORS AFFECTING VEGETABLES PRODUCTION DURING COVID-19 OUTBREAK IN MALAYSIA: A CASE STUDY IN SELANGOR - Malissa Durrani Muhamad Raizal; Nur Hazwani Mohammad Azam (International Journal of Accounting, Finance and Business, 2023)
Vegetables crops in Malaysia is commonly cultivated in purpose of meeting the local consumers’ demand. Vegetables production has been intensively grown by smallholder farmers in a specific region across Malaysia. However, the production of vegetables crops is severely disrupted by the sudden occurrence of COVID-19 pandemic. In Selangor, the implementation of Movement Control Order (MCO) has caused a significant impact on the vegetables production as the production dropped from the year 2019 to 2020. This study aims to identify the factors affecting vegetables production and determine the relationship between production factors and vegetables production during the pandemic. To achieve the objectives, the data for the study were obtained by constructive questionnaires from vegetables farmers in Selangor. Descriptive analysis provided the demographic analysis of the respondents while multiple regression was conducted to identify the relationship between the production factors. Based on descriptive analysis, 72.7% of the respondents are male with majority of them are above 60 years old and only have secondary education. The level of production also decreasing from 2019 to 2020 with 27.3% of respondents reported less than 5 mt of production in 2020 as compared to 25.3% in 2019. It is found that cultivated land size, capital, labor, fertilizer application and government policy have significant relationship towards vegetables production.